"In sober dignity": the Irish Brigade, ethnicity, and the Irish Catholic temperance movement in the Civil War era. Issue 2 (4th May 2022) - Smithmyer, Abbi
ABSTRACT: This study shows how Irish Catholic temperance groups challenged nativist stereotypes towards Irish immigrants. Irish Americans used abstinence to achieve a respectable reputation among native-born Americans in the Civil War era. By linking Civil War service with the temperance efforts of Irishmen who fought for the Union Army, prominent members of the ethnic group demonstrated that Irish Americans were respectable and virtuous citizens of the United States throughout the Civil War era.